Bullying Behaviour of Adolescents Based on Gender, Gang and Family - Kadek Ayu Erika; Dian Atma Pertiwi; Tuti Seniwati (Jurnal Ners, 2017)
Introduction: Bullying is a social problem which is part of aggressive violent behaviour done continuously and have negative impact to victims and its subject and happened at school. This study aimed to know the description of knowledge and adolescents behavior about bullying based on their age, gang, and family.Methods: This study used analytic descriptive design with number of sample was 246 adolescents from grade 1, 2, 3 of senior high school which used stratified random sampling. Instruments of this study were knowledge questioner, and modified of The Bullying Prevalence Questionnaire in guttman and likert scale. Data analysis used cross tabulation.Results: Data show that adolescents have a good knowledge (93.9%) and less (6.1%). Bullying subjects were 93.9% and victims 94.7%. Forms of verbal bullying indicated the subjects (93.1%) and victims (92.3%). Bullying subjects majority occurred in males (94.1%) and women become victims (96.3%). Numbers of bullying subjects do not have a gang (94.5%), while those with gang as victims (95.2%). There were five adolescents who live in stepfamilies become subjects and victims of bullying.Conclusion: The majority of adolescents have good knowledge about bullying, bullying form the vast majority were verbal bullying with subjects and victims of bullying who occurs in all classes. The majority of bullying subjects do not have a gang, and as the majority of victims have a gang. Almost all adolescents with different family types become subjects and victims of bullying. Therefore, an intensive educational effort and spiritual needs to be done to change the behavior of adolescents to be adolescents with well character.